Appealing multimodal languages to access first year university students’ understanding of mathematical concepts in Costa Rica - Alfaro Víquez, Helen (2018)
The current situation regarding the lack of skills and mathematical knowledge that students have when entering the university, has caused that institutions of higher education take certain actions such as the inclusion of courses or content reduction. Most of the measures taken involve curricular changes or partitioning of contents. However, the problem requires also methodological changes that improve students' understanding. Therefore, following the mathematical proficiency and the multimodal approach theories, this qualitative research seeks to use the written languaging exercises that involve the use of natural, symbolic and pictorial languages as a tool to address this situation, promoting the active participation of students to justify and explain their procedures. The aim is to find out student and teachers’ experiences with the languaging exercises. This research was conducted in a Calculus 1 course of the University of Costa Rica, with 33 engineering students and two teachers. The design involves three instruments to collect information: 17 exercises of languaging designed on the topic of derivatives that were applied during the class or as homework during seven weeks, a questionnaire with 18 Likert scale statements and six open ended questions answered by students after the applications of the exercises, and a semi-structured interview for the teachers. The results indicated positive experiences of the participants. They expressed that the languag ing exercises are useful to make learning more meaningful, to identify the different ways in which student’s appropriate knowledge, as well as the misconceptions they have, through the explanations they provide. The exercises also favor, in their opinion, the development of analytical, reasoning, abstract thinking and metacognition skills